Improvement of Radiological Teaching – Effects of Focusing of Learning Targets and Increased Consideration of Learning Theory Knowledge - Wirth, Stefan; William, York-Alexander; Paolini, Marco; Wirth, Kathrin; Maxien, Daniel; Reiser, Maximilian; Fischer, Martin R. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Purpose Based on evaluation and examination results of students, a necessity for improvement of so far purely instructor-based radiological teaching at the local institution was determined. Aim of our study was to use one out of eight seminars to exemplify adaptation of the teaching concept according to learning theory knowledge, to determine the resulting effects and to interpret them.Materials and methods The institutional review board approved the prospective study of the seminar conversion, which was performed after the end of the winter semester 2015/2016. Didactically, this included a course split into online preparation, attendance phase and online follow-up with integration of interactive scaffolding, practice-oriented clinical teaching according to Stanford, Peyton skills transfer and extensive feedback into the attendance phase. At the beginning and at the end of each course, each student filled in identical, standardized questionnaires (n = 256 before and after conversion) using a 5-point Likert scale (1: very good; to 5: deficient) and additionally answered two randomly chosen written examination questions from a content-adapted questionnaire pool of the last five years. For statistical evaluation, the Mann-Whitney U-Test was used for evaluation data and Fisher's Exact test for exam questions.Results Before/after conversion, the subjective total evaluation score of students was 3.22 (mean value) ± 1.51 (standard deviation) / 1.66 ± 0.78 (p < 0.001) and the objective proportion of correctly answered examination questions in the respective cohort at the beginning of the seminar 37.7/53.9 % and at the end of the seminar 55.1/84.6 % (p < 0.001).Conclusion The conversion of the test seminar resulted in both a better evaluation of the teaching unit by the students (evaluation) and a considerably higher rate of correctly answered examination questions from past state examinations (learning success). This supports transferring the concept to comparable teaching units.Key points Citation FormatZiel Basierend auf Evaluationen und Prüfungsleistungen der Studierenden wurde eine Notwendigkeit zur Verbesserung einer institutionell bislang rein frontalen radiologischen Lehre abgeleitet. Ziel unserer Studie war es, zunächst exemplarisch eines von acht Seminaren verstärkt nach lerntheoretischen Erkenntnissen auszurichten, die resultierenden Effekte festzustellen und zu interpretieren.Material und Methoden Die Ethikkommission erteilte ein positives Votum zur prospektiven Studie der Seminarumstellung, die nach dem Wintersemester 2015/2016 durchgeführt wurde. Didaktisch wurde in Online-Vorbereitung, Präsenzphase und Online-Nachbereitung aufgeteilt und hierbei interaktives Scaffolding mit praxisbezogenem Clinical Teaching nach Stanford, Skillsvermittlung nach Peyton und ausgedehnter Feedbackeinsatz in die Präsenzphase integriert. Jeweils zu Beginn und am Ende der Präsenzveranstaltungen füllte jede/r Studierende (je n = 256 vor und nach Umstellung) identische, standardisierte Fragebogen unter Verwendung einer 5-Punkte Likert-Skala (1: sehr gut, …, 5: mangelhaft) aus und beantwortete zusätzlich jeweils zwei zufällig geloste schriftliche Prüfungsfragen aus einem inhaltlich abgestimmten Staatsexamen-Fragenpool der letzten fünf Jahre. Zur statistischen Auswertung wurde der Mann-Whitney-U-Test für Evaluationsdaten und Fisher’s-Exact-Test für Prüfungsfragen verwendet.Ergebnisse Vor/nach Umstellung betrug die subjektive studentische Gesamtbewertung 3,22 (Mittelwert) ± 1,51 (Standardabweichung) / 1,66 ± 0,78 (p < 0,001) und der objektive Anteil korrekt beantworteter Prüfungsfragen in der jeweiligen Kohorte zu Beginn des Seminars 37,7/53,9 % sowie am Ende des Seminars 55,1/84,6 % (p jeweils < 0,001).Schlussfolgerung Die Umstellung des Testseminars führte sowohl zur besseren Bewertung der Lehrveranstaltung durch die Studierenden (Evaluation) als auch zu einer erheblich höheren Quote korrekt beantworteter Prüfungsfragen aus vergangenen Staatsexamina (Lernerfolg). Dies motiviert zur Konzeptübertragung auf vergleichbare Lehrveranstaltungen.Kernaussagen Zitierweise
Keywords: radiological and medical education; curricular improvement; emergency radiography of the chest